2023
DOI: 10.3390/bios13040465
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Surface Design in Surface Plasmon Resonance (SPR) Sensing

Abstract: Surface plasmon resonance (SPR) comprises several surface-sensitive techniques that enable the trace and ultra-trace detection of various analytes through affinity pairing. Although enabling label-free, sensitive detection and real-time monitoring, several issues remain to be addressed, such as poor stability, non-specific adsorption and the loss of operational activity of biomolecules. In this review, the progress over sensor modification, immobilization techniques and novel 2D nanomaterials, gold nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 107 publications
(137 reference statements)
0
10
0
Order By: Relevance
“…Despite these limitations, SPR biosensors continue to be highly valuable in various research and diagnostic applications. Researchers and developers should consider these disadvantages when selecting the most appropriate biosensor technology for their specific needs and design experiments to address potential challenges. , …”
Section: Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, SPR biosensors continue to be highly valuable in various research and diagnostic applications. Researchers and developers should consider these disadvantages when selecting the most appropriate biosensor technology for their specific needs and design experiments to address potential challenges. , …”
Section: Biosensorsmentioning
confidence: 99%
“…Researchers and developers should consider these disadvantages when selecting the most appropriate biosensor technology for their specific needs and design experiments to address potential challenges. 154,155 Dutra et al utilized an SPR biosensor for the real-time and rapid detection of human troponin T. They improved the SPR biosensor by using a streptavidin-terminated self-assembled monolayer to immobilize biotinylated antitroponin T monoclonal antibodies. The result of this assay demonstrated that the improved SPR biosensor had a detection range for troponin T of 0.03 to 6.5 ng/mL.…”
Section: Optical Biosensorsmentioning
confidence: 99%
“…4–10 LSPR has found numerous applications in diverse fields, including photonics, chemistry, medicine, and energy harvesting. 11–14 The full width at half maximum (FWHM) of LSPR is an important parameter that should be carefully optimized for specific device-based applications. 11–17 A narrower resonance peak is required for more precise real-time sensing and accurate analyte detection.…”
Section: Introductionmentioning
confidence: 99%
“…11–14 The full width at half maximum (FWHM) of LSPR is an important parameter that should be carefully optimized for specific device-based applications. 11–17 A narrower resonance peak is required for more precise real-time sensing and accurate analyte detection. 11,16 In contrast, a broad FWHM can be advantageous for LSPR-based energy conversion applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation